BONE HEALTH FACTORS IN ADOLESCENTS FROM VARNA - Darina N. Hristova; Teodorа T. Dimitrova; Panayot N. Nikolov (Peytchinski Publishing, 2018)
Purpose: The purpose of our study is to research nutritional behavior and PA in a representative sample of 12th grade students (18-20 years of age) from Varna. Methods: We used two questionnaires: on the frequency of food consumption and on the assessment of physical activity. We applied the International Physical Activity Questionnaire, recommended from WHO. Results: The survey includes 401 young people. These are 11.2% of all 12th grade students in Varna. Тwo portions or more per day of dairy products are consumed by 94.5% young men and 48.7% of young women. More than half of the girls have inadequate intake of bioavailable calcium. The lowest consumption is in the underweight female group. There is a significant positive correlation between low milk consumption and Body Mass Index (BMI) in girls (r = 0.409 **, p <0.001). Around 1/3 of the youngsters have an adequate intake of fish. The remaining 63.1% of young boys and 68% of girls are at risk of vitamin D deficiency during the winter season. Low levels of PA were measured in 43.7% of the boys and 20.1% of girls. Conclusions: The eating behaviour of adolescents from Varna shows a shortage of important nutrients for bone development. The consumption of fish is low for both sexes, and ½ of the girls do not consume enough dairy products. Recommendations for optimal PA (high to moderate) were met in 79.90% of young men and 56.30% of girls. Nearly ½ of young women have low PA and are at risk for their bone health.